2013
DOI: 10.1002/ece3.557
|View full text |Cite
|
Sign up to set email alerts
|

Modeling ecological minimum requirements for distribution of greater sage‐grouse leks: implications for population connectivity across their western range, U.S.A

Abstract: Greater sage-grouse Centrocercus urophasianus (Bonaparte) currently occupy approximately half of their historical distribution across western North America. Sage-grouse are a candidate for endangered species listing due to habitat and population fragmentation coupled with inadequate regulation to control development in critical areas. Conservation planning would benefit from accurate maps delineating required habitats and movement corridors. However, developing a species distribution model that incorporates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
161
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(174 citation statements)
references
References 42 publications
10
161
3
Order By: Relevance
“…In two cases, we found that sagebrush cover <30% impacted dispersal, with a 10% threshold in the third, suggesting that sagebrush cover <10%–30% reduces gene flow. As with the habitat thresholds, sage‐grouse are capable of dispersal through habitats in which they are unlikely to persist (suggested persistence thresholds are in the range of 40%–65% sagebrush cover; Aldridge, Nielsen, & Boyce, 2008; Wisdom et al., 2011; Knick, Hanser, & Preston, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In two cases, we found that sagebrush cover <30% impacted dispersal, with a 10% threshold in the third, suggesting that sagebrush cover <10%–30% reduces gene flow. As with the habitat thresholds, sage‐grouse are capable of dispersal through habitats in which they are unlikely to persist (suggested persistence thresholds are in the range of 40%–65% sagebrush cover; Aldridge, Nielsen, & Boyce, 2008; Wisdom et al., 2011; Knick, Hanser, & Preston, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Energy development reduces the amount of available habitat and increases anthropogenic disturbance, which reduces lek attendance, nest initiation rates, nesting success, and survival of adult females (Lyon and Anderson 2003, Holloran 2005, Kaiser 2006, Walker et al 2007, Doherty et al 2008, Harju et al 2010, Holloran et al 2010. Additionally, sage-grouse are highly sensitive to other types of human disturbance, such as roads, residential areas, pipelines, vehicle traffic and noise (Johnson et al 2011, Blickley et al 2012, Knick et al 2013, Taylor et al 2013. Following multiple petitions for listing under the Endangered Species Act (ESA) and several years of litigation, the US Fish and Wildlife Service (USFWS) issued a listing of ''warranted but precluded'' in 2010, and agreed to deliver a final decision in 2015 that will determine whether the sage-grouse is listed under ESA or removed as a candidate species.…”
Section: Introductionmentioning
confidence: 99%
“…Endangered Species Act. Occurrence of Greater Sage-Grouse is associated most closely with presence of relatively extensive, contiguous stands of mature sagebrush (Aldridge and Boyce 2007, Hanser et al 2011, Knick et al 2013. Preventing the species' listing is among the highest priorities of resource agencies in the Great Basin.…”
Section: Introductionmentioning
confidence: 99%